Ferromagnetic Resonance Vector Magnetic Sensor with High Sensitivity and Ultrawide Working Range. Issue 5 (15th October 2021) - Wen, Tao; Wang, Zhiguang; Du, Qin; Su, Wei; Guan, Mengmeng; Zhao, Shishun; Wu, Jingen; Hu, Zhongqiang; Zhou, Ziyao; Liu, Ming
Abstract: Large working range is of vital importance for magnetic sensors when exposed to complicated magnetic field profile, especially in automation and power industry where large field variation is frequently encountered. The design for traditional magnetic sensors, e.g., magnetoresistive and fluxgate magnetometers, utilizes ferromagnetic materials with ultrahigh permeability to maximize the field sensitivity, resulting in strictly confined dynamic range due to limited saturation field. Here, an integratable ferromagnetic resonance (FMR) prototype magnetic sensor with high sensitivity and theoretically unlimited working range is reported. An ultrawide working range (> 450 mT) which is more than two orders larger than that of commercial sensors with similar field resolution is experimentally verified. Moreover, the FMR magnetometer is a vector sensor in contrast to the traditional scalar sensors based on magnetic resonance. With a navigating magnetic field of 50 μ T (ca. the Earth's magnetic field), the resolution for azimuth angle is 0.006° . Compared with traditional nuclear magnetic resonance and electron paramagnetic resonance sensors with large size and high power consumption, the compact FMR sensor with large dynamic range and high sensitivity has much broader application prospects, especially in magnetically harsh environments. Abstract : Magnetic field sensor based on ferromagnetic resonance is developed based on yttrium iron garnet films on a coplanar waveguide. An ultrawide working range which is more than two orders larger than that of commercial sensors with similar field resolution has been experimentally verified. With a navigating magnetic field of 50 μT (Earth's magnetic field), the resolution for azimuth angle is 0.006°.